(untitled) (Third Sector Social Economic Review, 2026)
This study re-evaluates deviations from rational investor behavior during periods of crisis and market bubbles by integrating traditional finance, and behavioral finance within a comprehensive framework. The study examines the behavioral underpinnings of these deviations from rationality, exploring their impact on market conditions and risk factors. It assesses, from various perspectives, how traditional finance theories—guided by the premise of rational investor behavior—remain relevant, while also acknowledging that investment decisions within financial markets are influenced by some psychological factors. Historical instances of deviation from rational investor behavior during crises and bubbles, along with their consequential effects on the markets, are investigated. Traditional finance theories posit that investors engage in rational, consistent, and utility-maximizing decision-making. However, behavioral finance theories fundamentally challenge these assumptions by illustrating that investors are susceptible to systematic cognitive biases, emotional responses, and intuitive decision-making processes. This study reconciles the normative rationality models of traditional finance with the descriptive insights from behavioral finance by incorporating approaches from psychology, including bounded rationality, dual-process thinking, decision-making under uncertainty, and the concept of regret. The findings suggest that investor behavior is not solely dictated by financial models but is a multifaceted phenomenon shaped by cognitive, emotional, and social factors.